Sri Ksetra:The Ancient City of Pyu Rising in a Marvelous Dignity for Myanmar-Buddhism - Nyunt, Thiri (Journal of International Buddhist Studies, 2015)
All nations and nationalities in the world stand on their own dignities with some prominent buildings, renowned places, beautiful culture and legendary heroes. With splendid dignity, each land persists in elegance on the world’s map. Every dignified building or renowned place narrates about its respective ancient story. Some of them connected with religions are especially more fabulous than other things in the world. It is because religious buildings or places enable visitors to bear faith and peace as going there. In Myanmar, Pyu Ancient Cities includes the remains of three brick, walled and moated cities of Halin, Beikthano and Sri Ksetra located in vast irrigated landscapes in the dry zone of the Ayeyarwady (Irrawaddy) River basin. They reflect the Pyu Kingdoms that flourished for over 1,000 years between 200 BC and AD 900. In this paper, Sri Ksetra, one of the magnificent ancient city in Myanmar, which are put in the list of the world’s heritage, will be made known as how long has been existed, how becomes eminent, and how importance for the Buddhism and human.